Effects of biological and environmental factors on the variability of Paralonchurus brasiliensis (Sciaenidae) density: An GAMLSS application - Costa, Eudriano F.S.; Teixeira, Gustavo M.; Freire, Fúlvio A.M.; Dias, June F.; Fransozo, Adilson [UNESP] (Elsevier, 2022)
The hypothesis of this study was based on the premise that complex interactions between biological and environmental factors may explain variability in fish population dynamics. To test this, Paralonchurus brasiliensis (Sciaenidae), a keystone species associated with coastal waters, was used as a model fish species. Generalized Additive Models for Location, Scale and Shape were performed to evaluate relationships among biological and environmental variables. Fish biomass, repletion index (RI), hepatosomatic index (HSI), condition factor (K) and sex ratio was in models as biological factors whereas water temperature, salinity, organic matter, grain size and depth were included as environmental variables. The results revealed significant effects of biological and abiotic factors on population density of P. brasiliensis. The selected model explained 94% of the variability in the explanatory variables. Fish biomass, HSI and K were the most important biological factors, whereas temperature and organic matter were the most important abiotic factors. Variability in fish density suggests that HSI and K both could be used as an additional ecosystem indicator of environmental status (food availability) and fish population health. We also highlight the importance of using robust and flexible statistical methods to model fish population dynamics and the need to incorporate biological and environmental factors into fishery resource management.
Keywords: Atlantic Ocean; Demersal fish; Habitat condition; Population dynamics